Understanding mechanistic responses underlying diurnal photoprotection and photosynthetic plasticity among cacao genotypes under natural amazonian field conditions - Juan Carlos Suárez; José Iván Vanegas; Fabricio Eulalio Leite Carvalho (PLoS ONE, 2026)
Cacao ( Theobroma cacao ) is a key tree species for chocolate production and a vital income source for millions, especially in Africa and South America. In the Amazon, physiological studies on cocoa have focused on abiotic factors, but the comparison of clones in these environments is still in its infancy.This study examined the physiological responses of cacao clones to the typical diurnal conditions of the Colombian Amazon. We measured environmental, plant health, and chlorophyll fluorescence variables in 18 cacao clones using MultispeQ and Imaging-PAM throughout the day; we estimated F v /F m , ΦII, ETR, and NPQ t , calculated SLA, and quantified photosynthetic pigments. Significant phenotypic differences were identified in photosynthetic efficiency and morphology. High specific leaf area (SLA), linked to efficient energy capture and reduced transpiration, was observed in LUKER-40 and FGH-4. Chlorophyll a fluorescence approach, revealed differences in photochemical efficiency (F v /F m ) and excess energy dissipation. Genotypes like FGH-4, FSV-41, and IMC-67 showed high F v /F m and electron transport rates (ETR) (p < 0.05) under heat stress, indicating strong PSII functionality. Conversely, ICS-95 relied on non-photochemical quenching (NPQ t ) for heat dissipation. LUKER-50, with high carotenoid content, demonstrated resilience to oxidative stress. Variations in chlorophyll content affected light capture efficiency, with ICS-60 excelling in photosynthesis under high temperatures and excess light at noon. Leaf temperature regulation emerged as critical, with genotypes like LUKER-40 maintaining cooler leaves to avoid potential thermal damage. These traits highlight the acclimation of genotypes to high light and heat in the Colombian Amazon, with LUKER-50, ICS-95, FLE-3, and LUKER-40 identified as promising candidates for agroforestry in this region.